The efficacy of incorporating ultrasound-guided core biopsy into the clinical workflow of indeterminate thyroid tumors - Chun-Nan Chen; Min-Shu Hsieh; Yi-Hsuan Lee; Tsung-Lin Yang (Journal of the Formosan Medical Association, 2022)
Background: Ultrasound-guided core biopsy (USCB) is a minimally invasive sampling procedure which may help to confirm the diagnoses of the thyroid tumors with indeterminate results of ultrasound-guided fine-needle aspiration (USFNA). Although with potential advantages, the working protocol of introducing USCB in the routine practice has not been established yet. This study aims to evaluate the efficacy of USCB when it is included in the clinical workflow of assessing the thyroid tumors with indeterminate USFNA results after a long-term follow up. Methods: Between 2009 and 2016, consecutive patients receiving thyroid USFNA were reviewed retrospectively in the tertiary referral hospital. The patients, who finally received USCB for their thyroid tumors after repeated indeterminate USFNA results, were recruited. The important sonographic features in facilitating specific diagnoses by USCB, differentiating malignancy from benignity, and confirming origins of thyroid tumors were analyzed and the role of USCB was investigated. Results: Thirty-nine patients met the inclusion criteria were analyzed. The specific diagnoses were confirmed in 23 patients (59%) by USCB. Taller than wide, ill-defined margin and hypoechogenicity helped in differentiating malignant tumors and the latter two features were pertinent to the success of applying USCB for specific diagnosis. No sonographic features were able to differentiate the thyroid malignancy from extra-thyroid origins exclusively. Thyroid USCB facilitated clinical decision making in 37 of the 39 patients (94.9%) with indeterminate USFNA results. Conclusion: The USCB is a cost-effective sampling procedure for confirming the diagnosis of indeterminate thyroid tumors and their clinical management, especially for those malignancies from extra-thyroid origins.